Roles of NAC transcription factors in the regulation of biotic and abiotic stress responses in plants - Nuruzzaman, Mohammed; Sharoni, Akhter Most; Kikuchi, Shoshi (Frontiers in Microbiology, 2013)
NAC transcription factors are one of the largest families of transcriptional regulators in plants, and members of the NAC gene family have been suggested to play important roles in the regulation of the transcriptional reprogramming associated with plant stress responses. A phylogenetic analysis of NAC genes, with a focus on rice and Arabidopsis, was performed. Herein, we present an overview of the regulation of the stress responsive NAC SNAC/(IX) group of genes that are implicated in the resistance to different stresses. SNAC factors have important roles for the control of biotic and abiotic stresses tolerance and that their overexpression can improve stress tolerance via biotechnological approaches. We also review the recent progress in elucidating the roles of NAC transcription factors in plant biotic and abiotic stresses. Modification of the expression pattern of transcription factor genes and/or changes in their activity contribute to the elaboration of various signaling pathways and regulatory networks. However, a single NAC gene often responds to several stress factors, and their protein products may participate in the regulation of several seemingly disparate processes as negative or positive regulators. Additionally, the NAC proteins function via auto-regulation or cross-regulation is extensively found among NAC genes. These observations assist in the understanding of the complex mechanisms of signaling and transcriptional reprogramming controlled by NAC proteins.